Apontamentos históricos sobre a educação em áreas de várzea: considerações sobre as políticas públicas. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
This work aims to investigate and understand the floodplain areas in the Amazon for socioenvironmental sustainability, with emphasis on the influence of school education, based on public policies, in strengthening riverside communities. The research adopted a qualitative approach, supported by an extensive literature review. Floodplains are vital ecosystems in the Amazon, providing essential natural resources and sustaining regional biodiversity. Furthermore, they are central to the subsistence and cultural identity of riverside communities, who depend on these environments for fishing, agriculture and extractive activities. School education can play a key role as a catalyst to promote sustainable practices and empower communities to effectively manage their natural resources. Through educational programs adapted to local realities, it is possible to strengthen traditional and scientific knowledge about environmental management, encouraging the conservation and sustainable use of natural resources. The results highlight the importance of integrated public policies that recognize and respect the traditional knowledge of riverside communities, promoting a participatory and inclusive approach in the development of conservation and sustainable development strategies in the Amazon.
Keywords: Áreas de Várzea; Sustentabilidade; Comunidades Ribeirinhas; Educação na Amazônia; CNPQ:: CIÊNCIAS HUMANAS